Atividade respiratória de leucócitos como indicador de imunidade inata de pacu (Piaractus mesopotamicus) - Biller-Takahashi, J. D. [UNESP]; Takahashi, L. S. [UNESP]; Saita, M. V. [UNESP]; Gimbo, R. Y. [UNESP]; Urbinati, E. C. [UNESP] (FapUNIFESP (SciELO), 2013)
The present study evaluated the assay to quantify the respiratory burst activity of blood leukocytes of pacu as an indicator of the innate immune system, using the reduction of nitroblue tetrazolium (NBT) to formazan as a measure of the production of reactive oxygen species (ROS). In order to assess the accuracy of the assay, fish were challenged by Aeromonas hydrophila and sampled one week after challenge. The A. hydrophila infection increased the leukocyte respiratory burst activity. The protocol showed a reliable and easy assay, appropriate to determine the respiratory burst activity of blood leukocytes of pacu, a neotropical fish, in the present experimental conditions.
Leukocytes respiratory burst activity as indicator of innate immunity of pacu Piaractus mesopotamicus
Keywords: Cellular immunity; Fish immunology; Immune methodology